1964
DOI: 10.1063/1.1724945
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Diffusion-Controlled Processes in Liquids. Theoretical Consideration of Luminescent Systems: Quenching and Excitation Transfer in Collision

Abstract: The over-all behavior of reacting particles in solution is determined both by specific molecular properties and by probability of encounter. This paper presents an examination of the effect of the details of diffusion and locally inhomogeneous distributions on the over-all behavior of a system of reacting particles both for steady-state conditions and for the decay (or relaxation) phenomena subsequent to creation of an initial condition. The problem is formulated for the quenching of excited mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1966
1966
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…(3) for all the solvents and the values are given in Table 3. The values of p are less than unity for all the solvents, indicating reaction of quenching that is not solely controlled by material diffusion and may depend on other processes [16]. This fact is also observed by Table 3 The values of inverse of viscosity (Z À1 ), slope (k q t o ), quenching rate parameter k q , and quenching probability per encounter 'p'.…”
Section: Temperature (1c)supporting
confidence: 58%
See 1 more Smart Citation
“…(3) for all the solvents and the values are given in Table 3. The values of p are less than unity for all the solvents, indicating reaction of quenching that is not solely controlled by material diffusion and may depend on other processes [16]. This fact is also observed by Table 3 The values of inverse of viscosity (Z À1 ), slope (k q t o ), quenching rate parameter k q , and quenching probability per encounter 'p'.…”
Section: Temperature (1c)supporting
confidence: 58%
“…The probability of quenching per encounter 'p' and frequency of encounter 'k d ' are given by given by [16] …”
Section: Introductionmentioning
confidence: 99%
“…The same relation can be derived also from the discussions of one-dimensional random walks with partially absorbing walls given by Goodrich ll and Lehner. 12 By considering the balance between the diffusional flow of B*'s to a surface element and their reaction with A *, it can be shown that the boundary condition for our heterogeneous case is of the same form (2) where c is the density distribution function of B*, and the maximum value ~f k can be D/jJ., i.e., it may grow effectively to infinity. Rotational-diffusional flow does not make anv direct contribution to Eq.…”
Section: Probability Of Reaction Between a Single Pair Of Molecules Amentioning
confidence: 99%
“…As a simple example, the reaction of two types of molecules A and B has been considered for which the specific rate cons tan t k (fh, (2 ) can be expressed as a product of two functions…”
Section: General Solution Of the Diffusion Equationmentioning
confidence: 99%
“…As early as 1962 Burton and his coworkers [15,16] had constructed a pulsed radiolysis system which allowed diffusion-limited reactions to be followed on the nanosecond time scale. We suggest that, through pulsed radiolysis, it might be possible to generate reactive particles in situ in a pore or channel, and to follow their reactions.…”
Section: A Note On Applicationsmentioning
confidence: 99%